METODE PEMBELAJARAN TIDAK MENENTUKAN KEMAMPUAN MAHASISWA MELAKUKAN MANAJEMEN ASFIKSIA BAYI BARU LAHIR - Reni M.Kusuma (MEDIA ILMU KESEHATAN, 2013)
Background: Neonatal jaundice (icterus neonatorum) is acommon problem in infants in the first week after birth. Sixty percents of healthy infants born full term are at risk of neonatal jaundice. Bilirubin encephalopathy causes severe jaundice/kernicterus and the baby suffering from kernicterus will experience impaired growth and development. The Health education for mother is very important for improving the knowledge, disease prevention, and health improvement. Mother is expected to know and recognize the signsof icterus neonatorum so that she canbring the baby toget help at the health facilityas fast as possible. Objective: To reduce the risk of neonatal jaundice in Yogyakarta; to know the incidence of neonatal jaundice in breastfed infants, the effect of health education against therisk of neonatal jaundice; Methods:This study was an observational study with across-sectional design. Sampling used purposive sampling. The sample size was 115 pairs of mother-infant who met the inclusion and exclusion criteria. The data was collected using monitoring sheet sand check lists. Hypothesis test use dchi-square with p<0.05 and 95% Confidence Interval. Analysis of data used univari able and bivari ableanalyses. Results:There was adifference in the proportion of the risk of neonatal jaundice between mothers who received good health education and those who received inadequate health education. Mothers whoreceived in adequate health education were more likely tohave chances of neonatal jaundice by 2.1 times compared with mothers who received adequate health education. Conclusion: Mothers who received in adequate health education hada higher risk for neonatal jaundiceto occur compared with those who received adequate health education. Keyword: Healthy born baby, health education, neonatal jaundice (icterus neonatorum)